EDUCATIONAL TOURISM IN ISLAMIC EDUCATION TO IMPROVE STUDENTS’ CHARACTER - Westi Wiliyana Sari; Tonny Ilham Prayogo; Istikomah Istikomah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
Educational tourism is essential to the international tourism market, including in Indonesia. The educational tourism destinations are generally only in the regional tourism sector, cultural and natural tourism. However, the sector into tertiary institutions based on pesantren still needs to be significantly more attractive. With the existence of educational tours, it becomes a bridge between students and the general public in knowing universities-based pesantren. This includes supporting the government in developing educational tours to higher education institutions based on pesantren. This research is focused on university-based pesantren at the University of Darussalam Gontor, which implements pondok pesantren in building students with akhlaq and character. The quantitative approach is one of the approach techniques for hypotheses and data analysis relevant to the topic of writing based on the field. Therefore, sampling using simple random sampling and data collection using a student psychology scale as a simple regression model data analysis technique. The results of this study are the distribution of the percentage of educational tourism to university-based pesantren, which still needs to be developed. It is improving the information on university-based pesantren with activities that support students towards students with akhlaq and character following the education base of pondok pesantren and access to adequate information for easy access to information from the University of Darussalam Gontor with University-based pondok pesantren.